2022
DOI: 10.5603/fm.a2021.0065
|View full text |Cite
|
Sign up to set email alerts
|

Accessory right hepatic artery and aberrant bile duct in the hepatocystic triangle: a rare case with clinical implications

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In case 1 variant of our study, we observed the aRHA to be arising from the SMA, this can be categorised as type VI of the Michel classification and type III of the Hiatt's classification (Table 1). Similar cases were reported by various authors [16][17][18]. The results in the present study of this variant was in keeping with the findings of Michels (1.5%-7%) [3], Hiatt (10.6%) [4] In case 2 variant of the present study, we observed the rCHA to be arising from the SMA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In case 1 variant of our study, we observed the aRHA to be arising from the SMA, this can be categorised as type VI of the Michel classification and type III of the Hiatt's classification (Table 1). Similar cases were reported by various authors [16][17][18]. The results in the present study of this variant was in keeping with the findings of Michels (1.5%-7%) [3], Hiatt (10.6%) [4] In case 2 variant of the present study, we observed the rCHA to be arising from the SMA.…”
Section: Discussionsupporting
confidence: 93%
“…This rCHA branch of SMA giving off GDA and RHA and LHA at its termination along with an aLHA from the LGA therefore is a new subset hitherto unmentioned in any classification of the hepatic artery. aLHA from the LGA was reported by various authors [2,[17][18][19]34] .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant right hepatic artery (20% of patients) and aberrant bile duct (5%-8% of patients) are the other contents of the HCT. 6,7 Complete fat clearance of the HCT, the first requirement of the critical view of safety (CVS), is not evidence-based. 8,9 At present, the pre-and postdissection regions during LC are uniformly described by the term "HCT."…”
Section: Introductionmentioning
confidence: 99%
“…Within its fat pad is the right hepatic artery. The aberrant right hepatic artery (20% of patients) and aberrant bile duct (5%–8% of patients) are the other contents of the HCT 6,7 . Complete fat clearance of the HCT, the first requirement of the critical view of safety (CVS), is not evidence‐based 8,9 .…”
Section: Introductionmentioning
confidence: 99%